2014
DOI: 10.1115/1.4028496
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Transient In-Plane Dynamics of the Compression Ring Upon Its Tribological Performance

Abstract: Energy losses in an internal combustion engine are either thermal or parasitic. The latter are the mechanical inefficiencies, chiefly as the result of generated friction. Nearly half of these losses are attributed to the piston–cylinder system. During idle and at low engine speeds, friction is the major contributor to the overall engine losses. In particular, the rather small top compression ring accounts for a disproportionate share. Therefore, detailed understanding of compression ring tribology/dynamics (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…A study including these features was carried out by Baker et al 9,10 The generated contact pressures are also insufficient to cause any localised contact deflection as shown by Bolander et al 20 and Mishra et al 21 Therefore, the lubricant film shape is a function of its instantaneous gap and the ring axial profile, h s as…”
Section: Lubricant Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…A study including these features was carried out by Baker et al 9,10 The generated contact pressures are also insufficient to cause any localised contact deflection as shown by Bolander et al 20 and Mishra et al 21 Therefore, the lubricant film shape is a function of its instantaneous gap and the ring axial profile, h s as…”
Section: Lubricant Rheologymentioning
confidence: 99%
“…Therefore, the compression ring should conform well to the cylinder bore, thus resulting in increased friction. Baker et al 9,10 showed that compression ring elastodynamic modal behaviour and conformance to the bore surface results in a disproportionate share of parasitic losses from such a small contact conjunction.…”
Section: Introductionmentioning
confidence: 99%
“…Haddad and Tian [19] showed the validity of a one-dimensional analysis in such a case for rings with large length-to-width ratio; in excess of 30. In practice, the compression ring is subjected to in-radial plane modal behaviour and out-of-plane twist and bending [20][21][22]. Furthermore, in this analysis, the bore is considered to be a right circular cylinder, which is not the case in practice due to its out-of-roundness and cylinder block thermo-elastic distortion [23].…”
Section: Hydrodynamic Analysismentioning
confidence: 99%
“…The degrees of freedom employed for the in-plane case are the radial and tangential deflections, w and v [24,25], as GTP-16-1220 S. Theodossiades opposed to the out-of-plane deflection and ring twist. Further information on the in-plane ring dynamics can be found in Baker et al [24,25]. Additionally, whilst a finite element analysis is useful for validating the dynamics of the proposed methodology, the inclusion of a tribological model into the FEA would result in very long computation times.…”
Section: Introductionmentioning
confidence: 99%
“…The ring dynamic response for both the in-plane [24,25] and out-of-plane cases includes a forcing term, which incorporates any excitation applied to the relevant ring plane. This force profile is extracted from the tribological analysis post calculation of the external and internal forces acting upon the ring, as shown in Figure 3 for the ring's cross-section.…”
Section: Introductionmentioning
confidence: 99%